AB0499 Evaluation of the effectiveness of metaxodine in the hepatic toxicity due to methotrexate in patients with rheumatoid arthritis. (12th June 2018) - Parisi, S.; Ditto, M.C.; Scarati, M.; Priora, M.; Enrico, F.
Abstract : Background: Methotrexate inhibits the metabolism of purines resulting in the accumulation of adenosine; it also inhibits the activation of T cells and suppresses the expression of intercellular adhesion molecules for T cells. Side effects may show up during the treatment and among them there is hepatic toxicity, characterised by an increase of AST and ALT; such increase is usually asymptomatic but it may lead to a suspension of the treatment. Metadoxine (MTDX) is a drug which is used in order to treat both acute and chronic alcohol intoxication; it also prevents the inactivation of ATP from acetaldehyde and pyroglutamic acid. MTDX also showed to improve hepatic function markers and to decrease oxidative stress leading to a protective effect against radicals. Objectives: The aim of this preliminary study was to evaluate the possible effect of MTDX on hepatic function in patients affected by RA in therapy with MTX. Methods: The study involved the recruitment of patients affected by RA in treatment with MTX; a following random selection of a subgroup of patients who took MTDX (500 mg twice a day for 28 days, from the 5th to the 8th week of therapy with MTX) was performed. All the patients underwent a 12-week-follow up in which these parameters were evaluated: demographics, blood tests required for MTX in accordance with datasheets (especially AST and ALT), CRP, ESR, ACPA, numbers of swollen and tender joints, concomitant medications (NSAIDs and steroids) and the degree of disability (HAQ, table 1). Results: 24 patients affected by RA (20 women), with an mean age of 51.3 years (±14.1) and mean MTX dose of 12.3±2.6, were recruited. 70.3% took GC with a medium dosage (3.72±2.71). Among these 24, 13 patients were underwent MDTX 500 mg twice a day from the 5th to the 8th week. Patients treated with MTDX+MTX showed a significant decrease of hepatic markers (AST Δ−18.38 p=0.004 – ALT Δ−19.23 p=0.004) compare with patients with MTX only (AST Δ−4.27 p=0.110 – ALT Δ−6.09 p=0.045) after a 12-week-monitoring, with no statistically significant difference concerning disease activity (table 2). Conclusions: This study showed the possible effect of MTDX in increasing the tolerance to the MTX without affecting its effectiveness. Its role may indeed have useful implications in patients who start the therapy with MTX or in those who develop hepatic toxicity during the treatment. Reference: [1] Fehér J, et al. The Beneficial Effect of Metadoxine in the Treatment of Fatty Liver Diseases. Reviews2009;3(1):65–79. Disclosure of Interest: None declared